Hubungan Umur dan Tingkat Pendidikan Terhadap Persepsi Wisatawan pada Kawasan Ekowisata Mangrove di Desa Linsowu Kecamatan Kulisusu Kabupaten Buton Utara - Yanti, Indri; Budiyanto; Rosmawati (Universitas Halu Oleo, 2021)
The purpose of this study was to determine the relationship between age and education level with visitor perceptions. This research was conducted on March to April 2020, located Mangrove Ecotourism Linsowu Village, Kulisusu District, North Buton Regency, Southeast Sulawesi Province. The population in this study were all visitors to Mangrove Ecotourism. Sampling was using accidental sampling method. The number of samples selected was 50 tourists with productive ages of 15 -49 years old. Data analysis using Pearson correlation analysis. The results showed that the variable age with the perception of mangrove ecotourism visitors had a correlation coefficient value of 0.95, meaning that the age variable with the visitorsperception had a very strong relationship. The correlation coefficient value of the education level variable with the perception of mangrove ecotourism visitors was 0.99, meaning that the variable level of education with the visitors perception has a very strong relationship